Adaptasi Sosial Orang Melayu dalam Bermukim di Bantaran Sungai: Studi Kasus: Kampung Mendawai dan Bansir Kelurahan Bansir Laut Kota Pontianak - Zairin Zain; Agus Azrianto (Universitas Muhammadiyah Palembang, 2024)
Malay is one ethnic that lives on riverbank of Kapuas. Settlements on riverbanks consist of physical elements such as buildings, river flow patterns, and their inhabitants, as well as non-physical elements in the form of rules and local wisdom. Rivers are environmental elements that shape settlement patterns in Mendawai and Bansir villages. Riverbanks are a place for social and cultural activities that illustrate a harmonious balance between humans and the natural environment. Natural conditions and physical/non-physical elements make residents in both villages adapt to current needs. This research explores forms of social adaptation in the settlement of Malay people on riverbanks. The method used in this research is a descriptive and qualitative approach, which describes the existing conditions of two Kampung, Mendawai and Bansir, in the Bansir Laut Subdistrict using the adaptation strategy theory. Data was collected by field observation, literature study, and digital tracing. The results of this research illustrate the social adaptation of the people in Mendawai and Bansir villages according to the environmental conditions on the riverbanks. The village circulation route of both Kampung is maintained with Gertak and Steher as essential elements of the environment, which is experiencing changes as a manifestation form of the social adaptation of the Malay people on the banks of the Kapuas River.